PENGARUH PADUAN JENIS PLASTIK PP, HDPE, DAN LDPE DAUR ULANG TERHADAP SIFAT MEKANIK BALOK PLASTIK HASIL INEJCTION MOLDING - Hendra; Basuki Abdulah; Shofiatul Ula; Reski Septiana; Hernadewita; Hermiyetti (AUSTENIT, 2025)
The abundant amount of plastic waste and the high environmental problems it caused encourage the efforts to utilize recycled plastic materials in various applications, including the manufacture of plastic block produced using injection molding. This study aimed to analyze the effect of a mixture of recycled plastic types (PP, HDPE, and LDPE) on the mechanical properties of plastic blocks. Two of the three types of recycled plastic used were combined with a 1:1 composition and then molded into plastic blocks. Testing was carried out through tensile tests and impact tests to assess the tensile strength and toughness of the material. The results showed that the PP + HDPE alloy produced a tensile stress value of 26.2 MPa, a strain of 29.2%, and an elastic modulus of 89.6 MPa. While the average impact test value of this alloy reached 0.168 Joules/mm² with a maximum bending load of 3.94 kgf/cm². This alloy can be used as a reference material for manufacturing plastic blocks that have good mechanical properties.